Seed germination and seedling growth of Chiococca javanica (Rubiaceae) in relation to fruit maturation and media growth - R. SUBEKTI PURWANTORO (Smujo International, 2017)
Purwantoro RS. 2017. Seed germination and seedling growth of Chiococca javanica (Rubiaceae) in relation to fruit maturation and media growth. Nusantara Bioscience 9: 111-119. Chiococca javanica is a plant having ornamental potential. The seeds extracted from the fruits were classified according to maturity stage: Unripe - yellow; ripe - reddish; and over ripe - dark-red and seed germination were done in two germination media: sand and rice husk. The statistical approach was a randomized complete block design with three replications. Analysis of variance indicated that the seeds of C. javanica from the ripe and over ripe fruit had higher significances (P<0.05) on germination capacity, speed of germination, mean germination time, mean daily germination, peak value and germination value than the seeds from yellow fruits. The effect of growing media on germination process showed higher significance in sand than that in rice husk. Similarly, mean daily germination in sand was higher than that in rice husk. All seedling growth parameters of the seeds from ripe and over ripe fruit showed significant different on number of leaves, shoot length, diameter of seedlings, number of lateral roots, roots length, fresh weight and dry weight of plants than the seeds from unripe fruit.